Elementary and Intermediate Algebra: Concepts & Applications (6th Edition)

Published by Pearson
ISBN 10: 0-32184-874-8
ISBN 13: 978-0-32184-874-1

Chapter 7 - Functions and Graphs - 7.4 The Algebra of Functions - 7.4 Exercise Set - Page 476: 14



Work Step by Step

RECALL: $(f/g)(x)=\dfrac{f(x)}{g(x)}$ Thus, $(f/g)(x) = \dfrac{-2x+3}{x^2-5}$ To evaluate the given expression, substitute $3$ to $x$ in the equation above to obtain: $f(3)/g(3) \\= (f/g)(3) \\=\dfrac{-2(3)+3}{3^2-5} \\=\dfrac{-6+3}{9-5} \\=\dfrac{-3}{4} \\=-\dfrac{3}{4}$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.